Knowledge of students training to be health care professionals about AIDS transmission - Roupa, Zoi; Mylona, E.; Raftopoulos, Vasilios (My University, 2007)
Knowledge of how the HIV virus is transmitted and how we can protect ourselves against it will lead individuals to adopt appropriate sexual behavior, thus preventing transmission of HIV. An evaluation of this knowledge in a young population of reproductive age is fundamental when drawing up and assessing health education programs.
Keywords: HIV; Aids trasmittion